Outcomes of remotely delivered behavioral insomnia interventions for children and adolescents: systematic review of randomized controlled trials - Lah, Suncica; Cao, Thanh Vinh (Frontiers in Sleep, 2024)
Pediatric insomnia is common and can be effectively treated with behavioral therapies delivered face-to face. Such treatments could also improve children's mood, cognition, and quality of life, and caregivers' wellbeing. There is a discrepancy between high needs and limited access to pediatric behavioral insomnia treatments, which could be improved by provision of technology enhanced interventions. No study reviewed outcomes of randomized controlled trials (RCTs) of remotely delivered psychological treatments for pediatric insomnia. The current study aimed to examine (i) the outcomes of remotely delivered RCTs for pediatric insomnia/insomnia symptoms and (ii) whether gains made in treatment extend to functional correlates. We conducted a systematic review according to Cochrane and PRISMA guidelines. PsychINFO, PubMed/Medline and Cochrane CENTRAL databases were searched for RCTs reporting on remotely delivered behavioral treatments for insomnia and insomnia symptoms. Data was abstracted and the risk of bias were assessed in November 2022 and November 2023. Seven RCTs (nine manuscripts) involving 786 participants, with the mean age from 19.3 months to 16.9 years, were identified. Four different treatments were used. Risk of bias ranged from low to high and was the highest for the randomization process. Across studies, significant improvements were found in some (but not all) sleep parameters, namely: sleep quality and sleep efficacy on questionnaires and on actigraphy, despite heterogeneity of the treatments used, age of participants and instruments employed to assess outcomes. Improvements gained in treatments delivered remotely was compared to treatments delivered face-to-face in 3 studies and were found to be comparable or slightly lower. No worsening was observed on either objective or subjective measures of sleep, except for sleep onset latency and wake after sleep onset that improved on questionnaires but worsened on actigraphy in one study each. Children's mood improved across studies on parent and self-report measures. Other possible functional gains were understudied. Our study provides preliminary evidence of improved sleep following remotely delivered behavioral treatments for pediatric insomnia, and improvements in children's mood. Further research is needed to develop individualized treatments that will cater for different developmental needs and types of insomnia symptoms and examine not only group but also individual outcomes.